PELATIHAN PRESENSI ONLINE MENGGUNAKAN GOOGLE FORM DI YAYASAN PENDIDIKAN ISLAM AR-RIDHA - Adhar, Deni; Safrizal, Safrizal; Tanti, Lili; Fahrozi, Wirhan (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM Azramedia Indonesia, 2024)
The use of online attendance at several schools in the North Sumatra region can help efficiency in reducing physical materials (paper) and can be directly monitored/evaluated online. Currently, the school at the Ar-Ridha Foundation, one of the attendance methods implemented online, still uses WhatsApp to monitor online attendance. Due to many obstacles, sending attendance via WhatsApp is considered less effective. One of the barriers reported was the requirement for teachers to review each student's data submission individually. Using Google Forms to create virtual courses is one way teachers can apply online learning. Google Forms is a Google product. Google Forms is a free online program available to schools, non-profit organizations, and anyone with a Google Account. Using Google Forms will facilitate interaction between teachers and students. Google Forms makes it easy for students and teachers to stay in touch. Google Forms is a blended learning platform that Google developed for schools seeking to create, distribute, and assign paperless assignments